Waning vigilance and the disposition effect: Evidence from Thailand on individual investor decision making - Mark A. DeWeaver (2018)
We argue that existing explanations for the stock-market investor's disposition to "ride losers too long" are unsatisfactory because they abstract from any role for information processing. We propose instead that the disposition effect is a special case of "waning vigilance:" investors pay less attention to new information and analysis when making decisions about loss makers and are therefore slower to sell them when arguments in favor of holding cease to be valid. Results from a Thai individual investor survey are presented as empirical evidence in support of the hypothesis that vigilance is reduced following losses. © 2009 Elsevier Inc. All rights reserved.